Synthesis of 2-Isobutyl, 2-Isobutyl-5-aryl and 2-Isobutyl-5-thiol-1,3,4-Oxadiazoles - Hadil S. Aziz; Khalid M. Daoud (College of Education for Pure Sciences, 2007)
ABSTRACT In this paper the synthesis of some substituted 1,3,4-oxadiazoles from isobutyric acid was studied. The isobutyric acid was converted into the corresponding ethyl ester, which then treated with hydrazine hydrate in ethanol to give the acid hydrazide. The acid hydrazide was treated with substituted benzaldehyde to give the corresponding hydrazones. The synthesized hydrazones were then converted to 2-isobutyl-5-aryl-1,3,4-oxadiazoles by their reaction with PbO2. While treatment of acid hydrazide with formic acid and then with phosphorus oxychloride gave 2-isobutyl-1,3,4-oxadiazole. 2-Isobutyl-1,3,4-oxadiazole-5-thiol was synthesized by the reaction of acid hydrazide with carbon disulfide in potassium hydroxide solution. The structures of the synthesized compounds were confirmed by physical and spectral means.